Penerapan Case Method Dalam Meningkatkan Hasil Belajar Mahasiswa - Syam, Suehartono (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The counselors/professional guidance and counseling teachers is a teachers/counselors that can counseling and guidance services in schools on a planned, systematic and responsible manner. Professional counselors/teachers are educated in academic institutions that have effective and innovative learning methods. The case method can improve students' ability to analyze and solves problem. Thus study aims to determine how the description of student learning outcomes and whether the application of the case method can improve student learning outcomes in the course of the counseling program at school. The research method used is experimental research with a pre-post-test design group. Subjects were divided into two groups; the experimental group was 20 people and the control group was 20 people. The instruments used are tests and case study report evaluation sheets. The results showed that there was an increase in student learning outcomes being treated in the form of a case method. The application of the case method has a significant effect on improving student learning outcomes. This research is expected to be used in schools and colleges as well as to be an evaluation and development material for further researchers